Qualitative assessment of the dental health services provided at a dental school in Kerman, Iran - Maryam Rad; Jahangir Haghani; Arash Shahravan; Ali Khosravifar (Sociedade Brasileira de Pesquisa Odontológica, 2009)
Increasing the quality of the services provided in a Dental School can raise the satisfaction level of patients and consequently increase the level of their oral health. This study was conducted to evaluate the quality of dental care and services provided to patients referred to a Dental School in Kerman, Iran. In this qualitative study, face-to-face, in-depth interviews were conducted with 41 participants #&091;25 patients (P), 5 nurses (N), 6 dental academic staff (AS), and 5 dental students (S)#&093;. Then, the interviews were transcribed and analyzed, using content analysis of data. Data analysis in qualitative research involves breaking down the data and searching for codes and categories that are then reassembled to form themes. Both positive and negative themes emerged. Positive themes included: good infection control, service accessibility, patient appointments and visits were not assigned on merit, precise examinations, and comprehensive treatment plans. Negative themes included: long wait time, lack of options to pass waiting time, such as newspapers and television, an insufficient number of nurses, and not enough professors for supervision. In addition, the results of this study show that the patients and dental staff have high expectations in relation to dental services, and that implementation of these expectations would increase the overall satisfaction with and the quality of the level of services. Finally, some recommendations for improving services in the Kerman Dental School were given to the managing team of the Dental School.